Pengaruh Metode Pembelajaran Kooperatif Terhadap Motivasi Belajar Mahasiswa - Yunida Bawamenewi; Desi Arisandi Laga Nguru (Sekolah Tinggi Teologi IKAT Jakarta, 2021)
Abstratc This study aims to determine how strong the influence of the cooperative learning method is on the learning motivation of students of the 2019 Christian Religious Education Study Program at the Ecumenical Theology College. To achieve this goal, the researchers used quantitative methods through surveys using questionnaires guided by the results of interviews and distributing questionnaires with a population of 40 people and a sample of 30 people. The data was processed using IBM SPSS For Windows 16.0. To determine the effect of the cooperative learning method on the learning motivation of students of the 2019 Christian Religious Education Study Program at the Ecumenical Theology College. The results showed that the effect of cooperative learning methods on student learning motivation was categorized as very strong or correlated. The results of the analysis and hypothesis testing indicate that there is a significant effect between cooperative learning methods on the learning motivation of students of the 2019 Christian Religious Education Study Program at the Ecumenical Theology College with a very strong level of influence or there is a relationship between the two variables. AbstrakPenelitian ini bertujuan untuk mengetahui seberapa kuat pengaruh metode pembelajaran kooperatif terhadap motivasi belajar mahasiswa Prodi Pendidikan Agama Kristen angkatan 2019 di Sekolah Tinggi Teologi Ekumene. Untuk mencapai tujuan tersebut maka peneliti menggunakan metode kuantitatif melalui survei dengan menggunakan kuesioner yang berpedoman pada hasil wawancara, dan penyebaran angket dengan jumlah populasi 40 orang dan sampel 30 orang. Data diolah dengan menggunakan IBM SPSS For Windows 16.0. Untuk mengetahui pengaruh metode pembelajaran kooperatif terhadap motivasi belajar mahasiswa Prodi Pendidikan Agama Kristen angkatan 2019 di Sekolah Tinggi Teologi Ekumene. Hasil penelitian menunjukkan bahwa pengaruh antara metode pembelajaran kooperatif dengan motivasi belajar mahasiswa tergolong dalam kategori sangat kuat atau berkorelasi. Hasil analisis dan pengujian hipotesis menunjukkan bahwa terdapat pengaruh yang signifikan antara metode pembelajaran kooperatif terhadap motivasi belajar mahasiswa Prodi Pendidikan Agama Kristen angkatan 2019 di Sekolah Tinggi Teologi Ekumene dengan tingkat pengaruh sangat kuat atau ada hubungan antara ke dua variabel tersebut.